Cryogenic micro-calorimeters for mass spectrometric identification of neutral molecules and molecular fragments - Novotny, Oldrich; Allgeier, Steffen; Enss, Christian; Fleischmann, Andreas; Gamer, Lisa; Hengstler, Daniel; Kempf, Sebastian; Pies, Christian; Wolf, Andreas (Journal of applied physics, 2015)
We have systematically investigated the energy resolution of a magnetic micro-calorimeter (MMC) for atomic and molecular projectiles at impact energies ranging from E≈13 to 150 keV. For atoms we obtained absolute energy resolutions down to ΔE≈120 eV and relative energy resolutions down to ΔE/E≈10−3. We also studied in detail the MMC energy-response function to molecular projectiles of up to mass 56 u. We have demonstrated the capability of identifying neutral fragmentation products of these molecules by calorimetric mass spectrometry. We have modeled the MMC energy-response function for molecular projectiles and concluded that backscattering is the dominant source of the energy spread at the impact energies investigated. We have successfully demonstrated the use of a detector absorber coating to suppress such spreads. We briefly outline the use of MMC detectors in experiments on gas-phase collision reactions with neutral products. Our findings are of general interest for mass spectrometric techniques, particularly for those desiring to make neutral-particle mass measurements.
Gesehen am 04.07.2020